Phase I study of a new cancer vaccine of ten mixed peptides for advanced cancer patients. Issue 5 (26th April 2016) - Iwasa, Satoru; Yamada, Yasuhide; Heike, Yuji; Shoji, Hirokazu; Honma, Yoshitaka; Komatsu, Nobukazu; Matsueda, Satoko; Yamada, Akira; Morita, Michi; Yamaguchi, Rin; Tanaka, Natsuki; Kawahara, Akihiko; et al.
Abstract : A phase I study of a new cancer vaccine (KRM‐10), consisting of a mixture of 10 different short peptides, was conducted for patients with advanced gastrointestinal cancers. Primary or secondary endpoints included the dose‐limiting toxicity (DLT), or safety and immune responses, respectively. Peptide‐specific cytotoxic T lymphocytes (CTL) and immunoglobulin G (IgG), together with soluble inflammatory factors, were measured before and after vaccination. Twenty‐one patients were vaccinated with KRM‐10 at dose levels of 10 ( n  = 6), 20 ( n  = 8) or 30 mg ( n  = 7) of peptides every week for 6 weeks. No DLT were observed in the dose range evaluated. Common treatment‐related adverse events were a grade 1 injection site reaction in 15 patients, and fever in three patients (grade 1 in two patients and grade 2 in one patient). CTL activity to at least one peptide at the time of the third and sixth vaccination increased in 2 and 3 of 6 (10 mg), 2 of 8 and 4 of 6 (20 mg), or 2 and 1 of 6 (30 mg) patients, respectively. IgG levels, at the third and sixth vaccination, were also increased in 1 and 1 of 6 (10 mg), 2 of 8 and 4 of 6 (20 mg), or 1 and 3 of 6 (30 mg) patients, respectively. The KRM‐10 vaccine consisting of 20 mg of peptides was determined as the optimal dose for a coming phase II trial because of its safety, and also for demonstrating the most potent activity for augmenting the immune response of the three doses tested. This trial was registered at the UMIN Clinical Trials Registry as UMIN000008820. Abstract : A phase I study of a new cancer vaccine (KRM‐10), consisting of a mixture of 10 different short peptides, was conducted for patients with advanced gastrointestinal cancers. The KRM‐10 vaccine consisting of 20 mg of peptides was determined as the optimal dose for a coming phase II trial because of its safety, and also for demonstrating the most potent activity for augmenting the immune response of the three doses tested.